SLC26A9 in triple-negative breast cancer stem cells: a network pharmacology and molecular modeling study - Shen, Mimi; Ma, Zhiyuan; Cao, Yanghui; Wang, Lan; Feng, Guoli; Zhou, Zhengxing; Li, Leilei; Ji, Bei; Liu, Shuhui; Qin, Jiaqi; Wang, Qin; Liu, Xuemei; et al. (Frontiers in Bioengineering and Biotechnology, 2025)
Triple-negative breast cancer (TNBC) presents significant clinical challenges due to its high heterogeneity and lack of effective targeted therapies. Cancer stem cells (CSCs) play a crucial role in TNBC recurrence, metastasis, and drug resistance. However, the interplay between ion transport, microenvironmental regulation, and classical stemness pathways remains underexplored in existing reviews. In this work, we systematically integrated multi-omics databases, network pharmacology, protein–protein interaction (PPI) analysis, functional pathway enrichment, and molecular modeling to highlight the “bridging” role of SLC26A9 and its interacting proteins in TNBC stem cell self-renewal, drug resistance, and microenvironmental regulation. Comprehensive molecular docking and 100-ns molecular dynamics (MD) simulations demonstrated that the small molecule S9-A13 exhibited high affinity and stable binding to both SLC26A9 and tumor protein p53 (TP53), with docking affinities of −7.737 and −8.447 kcal/mol and molecular mechanics/generalized Born surface area (MM/GBSA) binding free energies of −34.47 and −25.65 kcal/mol, respectively. These results suggest that S9-A13 may act on the SLC26A9–TP53 axis to enable multi-target regulation of TNBC cancer stem cells. We further discuss the translational implications of such interventions, including safety profile considerations, potential off-target effects, and delivery strategies. In summary, this review provides a structured framework and testable hypotheses for developing SLC26A9-based multi-target precision therapies for TNBC CSCs, while emphasizing that these computational findings are hypothesis-generating and require rigorous experimental and clinical validation prior to translation.